Assessing the continuity of the blue ice climate record at Patriot Hills, Horseshoe Valley, West Antarctica. Issue 5 (2nd March 2016) - Winter, Kate; Woodward, John; Dunning, Stuart A.; Turney, Chris S. M.; Fogwill, Christopher J.; Hein, Andrew S.; Golledge, Nicholas R.; Bingham, Robert G.; Marrero, Shasta M.; Sugden, David E.; Ross, Neil
Abstract: We use high‐resolution ground‐penetrating radar (GPR) to assess the continuity of the Blue Ice Area (BIA) horizontal climate record at Patriot Hills, Horseshoe Valley, West Antarctica. The sequence contains three pronounced changes in deuterium isotopic values at 18 cal ka, 12 cal ka, and 8 cal ka. GPR surveys along the climate sequence reveal continuous, conformable dipping isochrones, separated by two unconformities in the isochrone layers, which correlate with the two older deuterium shifts. We interpret these unconformities as discontinuities in the sequence, rather than direct measures of climate change. Ice sheet models and Internal Layer Continuity Index plots suggest that the unconformities represent periods of erosion occurring, as the former ice surface was scoured by katabatic winds in front of mountains at the head of Horseshoe Valley. This study demonstrates the importance of high‐resolution GPR surveys for investigating both paleoflow dynamics and interpreting BIA climate records. Key Points: Katabatic winds have scoured unconformities in the internal annual layers of the Blue Ice Area (BIA) Unconformities evidence paleo BIA and represent breaks in the paleo climate record Ground‐penetrating radar should be used to examine BIA and interpret climate records